SISTEM PERPAJAKAN, NORMA DAN KEADILAN PADA PENGGELAPAN PAJAK - Sari, Luhdina Eka; S, Yayuk; Bau, Leonarda; mukoffi, ahmad mukoffie; Indah, Sri (Universitas Prof.Hazairin,SH Bengkulu, 2022)
Abstract Taxe play an important role in increasing state tax revenues, several factors that influence the occurrence of tax evasion, namely the uneven taxation system, low taxpayer norms and lock of tax justice. MSMEs in Tlogomas Malang Village partially This study uses quantitative methods. Determination of the sampel is abtained as many as 34 MSME taxpayers in Tlogomas Malang Village, the data collection technique used by the researcher is a questionnaire, the data analysis method used isregression multiple using SPSS 26 program. The result of the study prove that the taxation system has a significant effect on tax evasion with a tag value of 4.191, norms system has a significant effect on tax evasion with a tag value of thg 4.070 and fairness is significant effect on tax evasion with a value of 6.027 As for what needs to be considered by taxpayers, namely paying in time.